2013
DOI: 10.1091/mbc.e11-11-0914
|View full text |Cite
|
Sign up to set email alerts
|

MYADM controls endothelial barrier function through ERM-dependent regulation of ICAM-1 expression

Abstract: Myeloid-associated differentiation marker (MYADM) protein belongs to the MAL family and regulates raft domains in epithelial cells. Membrane rafts participate in inflammatory responses. This study shows that MYADM is expressed in endothelial cells and controls the endothelial barrier by regulating ICAM-1 expression through ezrin, radixin, and moesin proteins, connectors between plasma membrane domains and actin cytoskeleton.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 62 publications
(58 reference statements)
1
41
0
Order By: Relevance
“…Myelin-associated oligodendrocyte basic protein and myelin oligodendrocyte glycoprotein, two important myelin proteins in stabilizing the myelin sheath, showed no obvious alterations. Myeloid-associated differentiation marker (MYADM), which controls endothelial barrier function (Aranda et al 2013), was decreased in the HIP (81.2%) and HYP (89.1%) and increased in the PFC (141.0%) of the OVX rats (Fig. 3c).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Myelin-associated oligodendrocyte basic protein and myelin oligodendrocyte glycoprotein, two important myelin proteins in stabilizing the myelin sheath, showed no obvious alterations. Myeloid-associated differentiation marker (MYADM), which controls endothelial barrier function (Aranda et al 2013), was decreased in the HIP (81.2%) and HYP (89.1%) and increased in the PFC (141.0%) of the OVX rats (Fig. 3c).…”
Section: Resultsmentioning
confidence: 93%
“…MYADM controls endothelial barrier function (Aranda et al . ), and deficiency of Cavin‐1 induced dysfunction of the small arteries (Swärd et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5, K and L), including genes implicated in regulation of cell-matrix interactions ( Lgals1 , Fxyd5 ), metabolism ( Bola2, Echs, Eno1 , Gcsh ), and myeloid differentiation of HSPCs ( Myadm ). Myadm has recently been shown to regulate endothelial inflammation (Aranda et al, 2013), and increased expression of Myadm was observed in mesenchymal stromal cells derived from patients with myeloproliferative neoplasms (Ramos et al, 2017). Since inflammation-associated aging or “inflammaging” has recently emerged as a critical process driving HSPC aging phenotypes, it is likely that genes regulating endothelial inflammation may impact HSPC aging (Kovtonyuk et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Further analysis of our transcriptome data set revealed 13 such genes (Figure 5K-L), including genes implicated in regulation of cell-matrix interactions (Lgals1, Fxyd5), metabolism (Bola2, Echs, Eno1, Gcsh) and myeloid differentiation of HSPCs (Myadm). Myadm has recently been shown to regulate endothelial inflammation (Aranda et al, 2013) and increased expression of Myadm was observed in mesenchymal stromal cells (MSCs) derived from patients of myeloproliferative neoplasms (Ramos et al, 2017). Since inflammation-associated aging or 'inflammaging' has recently emerged as a critical process driving HSPC aging phenotypes, it is likely that genes regulating endothelial inflammation might impact HSPC aging (Kovtonyuk et al, 2016).…”
Section: Resultsmentioning
confidence: 99%